The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jid.2016.02.816
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells in Psoriasis Are an Expanded Population Exhibiting Diverse T-Cell–Suppressor Mechanisms

Abstract: Psoriasis vulgaris is an inflammatory skin disease caused by hyper-activated T-cells regulated by positive and negative mechanisms; while the former has been much studied, but the latter has not. We studied the regulatory mechanism mediated by myeloid-derived suppressor cells (MDSCs), especially having shown that MDSCs expanded in melanoma patients express DC-HIL, a critical mediator of T-cell suppressor function. We examined expansion of DC-HIL+ MDSCs in psoriasis and characterized their functional properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 49 publications
6
41
0
Order By: Relevance
“…Only limited numbers of previous reports discussed suppressive function of MDSCs in inflammatory disorders such as alopecia areata and arthritis (46)(47)(48). Very recently, MDSCs were reported to be expanded in psoriasis, infiltrating into lesional skin (49). They concluded that MDSC-mediated immunosuppression contributed to regulating hyperactivated T cells in psoriatic skin, which our results completely supported.…”
Section: Discussionsupporting
confidence: 83%
“…Only limited numbers of previous reports discussed suppressive function of MDSCs in inflammatory disorders such as alopecia areata and arthritis (46)(47)(48). Very recently, MDSCs were reported to be expanded in psoriasis, infiltrating into lesional skin (49). They concluded that MDSC-mediated immunosuppression contributed to regulating hyperactivated T cells in psoriatic skin, which our results completely supported.…”
Section: Discussionsupporting
confidence: 83%
“…MDSCs have important T-cell regulatory functions and have been suggested as a promising target in the development of novel therapeutics for MS. 10,17 However, current knowledge on the role of MDSCs in autoimmune diseases is limited and previous findings have been discordant. 12,13,15,17 Within the present study, we report data demonstrating differences in the frequency and absolute number of MDSC populations during the MS disease course, with addition changes to the functional status of Mo-MDSCs, including a loss in T-cell suppressive action, during progression of disease.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, in contrast to the situation in tumors, MDSC function in autoimmune diseases may involve both immunosuppressive and proinflammatory functions . A recent study reported that Mo‐MDSCs within the peripheral blood of patients with psoriasis exert reduced T‐cell suppressive ability, compared to melanoma‐derived Mo‐MDSCs . Similarly, Mo‐MDSCs derived from patients with inflammatory bowel disease failed to suppress T cells, which was associated with downregulation of CCAAT/enhancer‐binding protein beta (CEBP‐β) expression .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DC-induced cytokine production subsequently stimulated T-cell activity [4]. A cross-talk between DCs and T cells is thought to be responsible for the disease development [5]. Recently, the clearance of psoriasis using targeted immunotherapies demonstrates the important role of DCs in the pathogenesis of psoriasis.…”
Section: Introductionmentioning
confidence: 99%